Extension Time Presidential Office Through Delay General Elections in A Constitutional Democracy Perspective - Makmun, Fatimatuz Zakiya; Al-Fatih, Sholahuddin (Audito Comparative Law Journal (ACLJ), 2023)
A democratic system in the state, which uses the rule of law system (rechtstaat), is a constitutional democracy. Constitutional democracy is a system which respects and implements the mandate of the Constitution and applicable laws. Constitutional law aims to create discipline, peace and welfare in a country based on applicable law. Constitutional democracy is a system applied in many countries worldwide, without exception in Indonesia. In Indonesia, an applied system is a presidential one. Thus, the leader of the government is the president and vice president. The regulation on the terms of office for the president and vice president was written in Article 7 of the 1945 Constitution of the Republic of Indonesia. Meanwhile, the general election mechanism is written in regulated law number 7/2017. Regarding the terms of office for the president and vice president, minister of Coordinator for Maritime Affairs and Investment Luhut Binsar Pandjaitan made a public opinion that postponing the 2024 elections would have consequences in prolonging the terms of office for the president and vice president. Thus, this statement makes a public outreach because the opinion is based on big data of public opinion from social media and is not strengthened by the legally applied basis in Indonesia. This statement has violated the code of ethics of a minister based on the general principles of good governance (AAUPB) in Article 10 of Law Number 30/2014 concerning Government Administration. In addition, this statement caused public uproar and had implications for upholding the 1945 Constitution of the Republic of Indonesia and violating the values ​​​​of constitutional democracy in Indonesia.